Creating Defined Gaseous Environments to Study the Effects of Hypoxia on C. elegans - Fawcett, Emily M. (MyJove Corporation, 2012)
Oxygen is essential for all metazoans to survive, with one known exception(1). Decreased O(2) availability (hypoxia) can arise during states of disease, normal development or changes in environmental conditions(2-5). Understanding the cellular signaling pathways that are involved in the response to hypoxia could provide new insight into treatment strategies for diverse human pathologies, from stroke to cancer. This goal has been impeded, at least in part, by technical difficulties associated with controlled hypoxic exposure in genetically amenable model organisms. The nematode Caenorhabditis elegans is ideally suited as a model organism for the study of hypoxic response, as it is easy to culture and genetically manipulate. Moreover, it is possible to study cellular responses to specific hypoxic O(2) concentrations without confounding effects since C. elegans obtain O(2) (and other gasses) by diffusion, as opposed to a facilitated respiratory system(6). Factors known to be involved in the response to hypoxia are conserved in C. elegans. The actual response to hypoxia depends on the specific concentration of O(2) that is available. In C. elegans, exposure to moderate hypoxia elicits a transcriptional response mediated largely by hif-1, the highly-conserved hypoxia-inducible transcription factor(6-9). C .elegans embryos require hif-1 to survive in 5,000-20,000 ppm O(2)(7,10). Hypoxia is a general term for "less than normal O(2)". Normoxia (normal O(2)) can also be difficult to define. We generally consider room air, which is 210,000 ppm O(2) to be normoxia. However, it has been shown that C. elegans has a behavioral preference for O(2) concentrations from 5-12% (50,000-120,000 ppm O(2))(11). In larvae and adults, hif-1 acts to prevent hypoxia-induced diapause in 5,000 ppm O(2)(12). However, hif-1 does not play a role in the response to lower concentrations of O(2) (anoxia, operational definition <10 ppm O(2))(13). In anoxia, C. elegans enters into a reversible state of suspended animation in which all microscopically observable activity ceases(10). The fact that different physiological responses occur in different conditions highlights the importance of having experimental control over the hypoxic concentration of O(2). Here, we present a method for the construction and implementation of environmental chambers that produce reliable and reproducible hypoxic conditions with defined concentrations of O(2). The continual flow method ensures rapid equilibration of the chamber and increases the stability of the system. Additionally, the transparency and accessibility of the chambers allow for direct visualization of animals being exposed to hypoxia. We further demonstrate an effective method of harvesting C. elegans samples rapidly after exposure to hypoxia, which is necessary to observe many of the rapidly-reversed changes that occur in hypoxia(10,14). This method provides a basic foundation that can be easily modified for individual laboratory needs, including different model systems and a variety of gasses.